Simulation of the 'brittle-ductile transition in silicon single crystals using dislocation mechanics' - Comment - Hirsch, P; Roberts, S (Elsevier, 1997)
Y.B. Xin and H.J. Hsia modeled the brittle-ductile transition in silicon single crystals by symmetric emission of edge dislocations at a crack tip in {110}〈110〉 oriented specimens on slip planes passing through the crack tip and normal to the cleavage plane. They took into account the dislocation/dislocation interactions only between dislocations on one side of the crack plane. P.B. Hirsch and S.G. Roberts' comments on Xin and Hsia's paper on the simulation of the brittle-ductile transition in silicon single crystals using dislocation mechanics are presented.